Impact of Cash Holdings on the Value of Investors: Evidence from Pakistan Stock Exchange - Zohaib Naeem Babar; Dr. Muhammad Mahmood Shah Khan; Sheikh Khurram Abid; Shah Nawaz (Al-Qanṭara, 2022)
Abstract The primary purpose of this study is to find the relation between cash holding and the value of investors. The fixed-effect model is used to achieve the objectives of this research study. The study investigated the relationship between cash holdings and the value of investors by employing three portfolios: all firms, constrained firms, and firms with better investment opportunities. PSX listed firm-level data is taken, and the fix effect model in regression is applied. The study contributed a positive and strong relationship between the cash holding and the value of investors in all firms and constrained firms. But in the firms which have better investment opportunity has no relation between the cash and value. Earnings show a positive and significant relationship with the value in all the portfolios.